EVALUATION IS A COGNITIVE CATEGORY - Isakova Zilolakhon Zokirovna (Modern American Journals, 2025)
It is well known that evaluation is one of the fundamental cognitive categories of human thinking, as it allows assigning value to any object, event, or person. From the perspective of cognitive linguistics, evaluation is a cognitive process carried out based on the knowledge, experience, moral norms, and cultural values formed in the subject's mind. For example, expressions such as “kind child,” “heartless beauty,” or “sweet-tongued” convey not only descriptive meanings but also evaluative connotations.
Keywords: Cognitive linguistics, evaluation, cognitive category, concept, evaluative concepts, non-evaluative concepts,